2012
DOI: 10.4254/wjh.v4.i4.129
|View full text |Cite
|
Sign up to set email alerts
|

G6PT-H6PDH-11βHSD1 triad in the liver and its implication in the pathomechanism of the metabolic syndrome

Abstract: The metabolic syndrome, one of the most common clinical conditions in recent times, represents a combination of cardiometabolic risk determinants, including central obesity, glucose intolerance, insulin resistance, dyslipidemia, non-alcoholic fatty liver disease and hypertension. Prevalence of the metabolic syndrome is rapidly increasing worldwide as a consequence of common overnutrition and consequent obesity. Although a unifying picture of the pathomechanism is still missing, the key role of the pre-receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 74 publications
0
17
0
Order By: Relevance
“…The level of H6PDH, providing NADPH as a cofactor for 11βHSD1 activity, was unchanged in the adipose tissue of DHTtreated rats. We presume, however, that the elevation in adipose tissue CORT can still be attributed to the sustained activity of 11βHSD1, independently of H6PDH activity, owing to the greater availability of NADPH compared to NADPH + leading to predominant reductase reaction in vivo (Czegle et al, 2012). Apart from analyzing the prereceptor metabolism of glucocorticoids, we also assessed the level of GR expression and its intracellular redistribution (Nicolaides et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The level of H6PDH, providing NADPH as a cofactor for 11βHSD1 activity, was unchanged in the adipose tissue of DHTtreated rats. We presume, however, that the elevation in adipose tissue CORT can still be attributed to the sustained activity of 11βHSD1, independently of H6PDH activity, owing to the greater availability of NADPH compared to NADPH + leading to predominant reductase reaction in vivo (Czegle et al, 2012). Apart from analyzing the prereceptor metabolism of glucocorticoids, we also assessed the level of GR expression and its intracellular redistribution (Nicolaides et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The major regulators of hepatic glucose metabolism are the glucocorticoids that promote gluconeogenesis and stimulate the expression of key gluconeogenic genes, G6PC and PEPCK (phosphoenolpyruvate carboxykinase) . The local (pre‐receptor) glucocorticoid activation is mediated by 11β‐hydroxysteroid dehydrogenase type 1 (11βHSD1) that converts inert cortisone (in human) and dehydrocorticosterone (in rodents) into active cortisol and corticosterone, respectively, allowing glucocorticoid receptor (GR) to be activated. Studies have shown that the expression of 11βHSD1 is downregulated in HCC .…”
Section: Introductionmentioning
confidence: 99%
“…Results of both in vitro and in vivo studies show that the complex metabolism of the major stress hormone cortisol plays an important role in the pathomechanism of obesity‐related metabolic disorders . Influencing the involved enzyme activities is, therefore, considered as a novel strategy for the prevention or treatment of these diseases .…”
Section: Discussionmentioning
confidence: 99%